Memahami Istidraj di Era Kontemporer (Studi Tafsir fi Zhilalil Qur’an Karya Sayyid Quthb) - Fitri Hayati Nasution (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2022)
This article discusses how Istidrāj is interpreted according to Sayyid Qutb in Tafsir Fi Zhila ̅lil Qura ̅n and how Istidrāj is contextualized in contemporary life. While the purpose of this research is to find out the interpretation of Istidrāj according to Sayyid Qutb in Tafsir Fi ̅ Zhila ̅lil Qura ̅n and to find out how Istidrāj is contextualized in contemporary life. In this study the authors used a qualitative research method (library research) with an interpretation approach and a theological approach. The data collection technique in this study as a whole refers to the sources of the literature which consist of commentary books, dictionaries and also related books/journals discussing Istidrāj. The results of this research include: istidrāj is a power that is not properly calculated and forgotten by people who deny the verses of Allah SWT. He widened the horizon for them, gave them breadth and opportunity to commit transgressions and tyranny, to drag them little by little to destruction, and to trap them in deceit and schemes.